ASSESSING THE EFFECTIVENESS OF A NURSE-LED DIABETES SELF-MANAGEMENT EDUCATION PROGRAM ON GLYCEMIC CONTROL AND QUALITY OF LIFE - Amairaha Saqar A. Alanazi, RN1; Jameelah Mohaisen Alshammari, RN1; Hamida Ayada Al-Shammari, NT1; Abeer Munif Alshammary, NT1; Fadia Lafi Al Anazi, NT1; Budoor Lafi Antar Alenazy, NT1; Ahmed Sultan Sharan Aldhaferi, NT1, (Chelonian Research Foundation, 2022)
Background: Diabetes is a chronic condition that requires ongoing self-management to maintain optimal glycemic control and prevent complications. Diabetes self-management education (DSME) programs have been shown to improve patient outcomes, but the effectiveness of nurse-led DSME programs in Saudi Arabia has not been well studied. This study aimed to assess the effectiveness of a nurse-led DSME program on glycemic control and quality of life among patients with type 2 diabetes in a tertiary care hospital in Riyadh, Saudi Arabia. Methods: A quasi-experimental study design was used, with a pre-test and post-test evaluation of a convenience sample of 150 patients with type 2 diabetes. The intervention consisted of a 6-week nurse-led DSME program that included weekly group sessions and individualized counseling. The primary outcomes were glycemic control (measured by HbA1c) and quality of life (measured by the Diabetes Quality of Life questionnaire). Data were collected at baseline and at 3 and 6 months post-intervention. Results: Of the 150 participants, 120 (80%) completed the study. There was a significant reduction in HbA1c levels from baseline to 3 months (9.2% vs. 7.8%, p<0.001) and 6 months post-intervention (9.2% vs. 7.4%, p<0.001). There was also a significant improvement in overall quality of life scores from baseline to 3 months (3.2 vs. 4.1, p<0.001) and 6 months post-intervention (3.2 vs. 4.4, p<0.001). Participants reported high satisfaction with the program, with 95% stating they would recommend it to others. Conclusion: The nurse-led DSME program was effective in improving glycemic control and quality of life among patients with type 2 diabetes in Saudi Arabia. The program was well-received by participants and has the potential to be scaled up to other healthcare settings in the country. Further research is needed to evaluate the long-term sustainability and cost-effectiveness of the program. Keywords: Diabetes self-management education, type 2 diabetes, glycemic control, quality of life, nurse-led intervention, Saudi Arabia